The `Neo-Bureaucratic' state: professionals, managers and professional managers in schools, general practices and social work - Farrell, Catherine; Morris, Jonathan (2003)
The major shifts in public policy during the past two decades have led to equally momentous changes in policy provision and its supporting structures. This has been characterized as `post-bureaucracy' or `beyond bureaucracy'. This article argues that while new governance forms have emerged, they do not fit the post-bureaucratic model in that while they may have reduced hierarchy, paradoxically, the changes have increased bureaucratic tendencies. The new governance structures also have implications for public-sector workers, and specifically for managers and professionals. The article explores the impact of the new governance of these groups of public-sector professionals, teachers, and social workers and doctor (general practitioners). - Reproduced.
Keywords: Public administration; Bureaucracy